Marka hukukunda ihtiyati tedbirler - Şahin, Görkem Selim (My University, 2023)
Hukuk devletinin temel görevlerinden biri adaletin sağlanmasıdır. Ancak çeşitli sebeplerden ötürü adaletin yerine getirilmesi zaman alabilmekte ve hakkı ihlal edilen kişi yargılama süresi içinde mağdur olabilmektedir. Geçici hukuki korumaların varoluş amacı bu mağduriyetin önüne geçmektir. İhtiyati tedbirler geçici hukuki korumaların temel şekli olup yargılama sonunda verilen hükmün yerine getirilebilmesine hizmet eder. Marka hukuku gibi hızla gelişen ve ticaret dünyasında önemi hızla artan bir hukuk dalında ihtiyati tedbirlerin önemli bir yere sahip olduğu kuşkusuzdur. Bu çalışmada doktrin ve yargı kararları ışığında ihtiyati tedbirlerin fonksiyonu, şartları, marka hukukunda ihtiyati tedbir gerektiren sebepler, verilebilecek ihtiyati tedbir kararları ve yargılama süreci işlenmiştir.

One of the main duties of the rule of law is the provision of justice. However, due to various reasons, justice may take time to be served and the person whose right is violated may become a victim during the trial period. The purpose of temporary legal protections is to prevent this victimization. Precautionary measures are the basic form of temporary legal protection and serve to fulfill the judgment given at the end of the trial. There is no doubt that precautionary measures have an important place in a branch of law such as trademark law, which is rapidly developing and whose importance is increasing rapidly in the commercial world. In this study, in the light of doctrine and judicial decisions, the function and conditions of precautionary measures, the reasons requiring precautionary measures in trademark law, interim injunctions that can be given and the trial process are discussed.
Keywords: geçici hukuki koruma; ihtiyati tedbir; injunction; Law and legislation; marka; marka hakkı; marka hakkına tecavüz temporary legal protection; Markalar; trademark; trademark infringement; trademark right; Trademarks; Turkey; Türkiye; Yasa ve yasama